Preclinical Testing Strategies - Olejniczak, Klaus; Günzel, Peter; Bass, Rolf (Drug information journal, 2001)
Preclinical studies and testing strategies with and without the use of animal testing methods have the purpose of limiting risks whenever a new active substance is to be used as a medicinal product in humans. They should be designed in such a way as to achieve as early, risk-free, unproblematic, and economic a transition as possible from preclinical to clinical trials in medicinal products development. For this purpose the legitimate interests of subjects, patients, manufacturers (sponsors), and the scientific community as well as regulatory and competent authorities must be harmonized so as to achieve a course of action that is medicinally, ethically (also with respect to animal testing), and legally justified. The development of a new medicinal product is generally marked by a number of preclinical and clinical investigations; their sequential order with regard to contents and logic, the testing duration needed on an individual basis, and chronological overlaps when carrying out these studies are all to be determined. As every new active substance is a separate entity, investigations and testing strategies must be designed individually. The principle of flowcharts described in this text facilitates the development of a testing strategy adapted to a certain medicinal product by using decision-tree methods. At the same time, the flowchart principle allows for a structuring of the necessary scientific discussion between preclinical and clinical investigators as well as between sponsor and authorizing authority.